The Effect of Polyvinyl Alcohol Addition on the Optical Properties and Oxygen Detection Performance of Titanium Dioxide and Methylene Blue Nanocomposite Colorimetric Indicators - Kanokthip Boonyarattanakalin; Praphaporn Rattan; Maneerat Songpanit; Sutee Chutipaijit; Hideyuki Okumura; Keiichi N. Ishihara; Wanichaya Mekprasart; Wisanu Pecharapa (My University, 2024)
In this study, we investigated the impact of polyvinyl alcohol (PVA) incorporation on the optical properties and oxygen detection performance of a titanium dioxide/methylene blue (TiO2/MB) nanocomposite colorimetric indicator for packaging applications. The nanocomposite was synthesized via mechanical milling of TiO2 nanoparticles with MB and citric acid. PVA, at varying concentrations (0, 3, 9, and 14 wt%), was introduced during the wet milling process to produce a homogeneous composite film. Spin coating was employed to fabricate TiO2/MB nanocomposite films for oxygen detection evaluation. The influence of PVA loading on the films’ chemical functionalities and surface morphologies was assessed using Fourier-transform infrared spectroscopy (FTIR) and field-emission scanning electron microscopy (FE-SEM). The indicator’s activation process, involving a color change between bleached and colored states, and its recovery time were monitored via optical imaging and UV-VIS-NIR spectrophotometry. The results revealed that a PVA content of 9 wt% yielded well-defined films with enhanced stability of the TiO2/MB nanocomposite’s oxygen detection performance.
Keywords: Polyvinyl Alcohol; Titanium Dioxide; Methylene blue; Vinyl alcohol; Analytical Chemistry and Sensors